Marketing Communication of Golden Palace Hotel in Increasing the Number of Visitors after Lombok Earthquake - Fitriah Zaid Al Amudi; Hartin Nur Khusnia; Agus Purbathin Hadi (JCommsci - Journal Of Media and Communication Science, 2019)
Lombok earthquake in August 2018 affected physical damage and casualties. The earthquake also has an impact on the hotel industry as one of the regional economic sectors. Golden Palace Hotel is a hotel that is affected by physical damage resulting in a decrease in occupancy of hotel rooms so that the Golden Palace hotel wants to increase the number of visitors by making marketing strategies. This study aims to determine the marketing communication strategy of the Golden Palace Hotel in increasing the number of visitors after the Lombok earthquake. This study used descriptive qualitative method. Data collection techniques are done by interview, observation and documentation study. Data analysis used in this research is data reduction, data presentation, and conclusion drawing. The data validity test is done by triangulating sources and member checking. The results showed that the Golden Palace Hotel did the determination of communicators, making messages, determining the targets, choosing the media used and determining the desired goals based on the elements of communication and marketing communication services strategy.Keywords: Marketing Communications; Golden Palace Hotel; Lombok earthquake